Formulación de plan Estratégico basados en procesos sostenibles para la empresa Turismo Colombiano SAS de la ciudad de Santa marta años 2021-2024 - Arboleda Mejía, Elsy Katiana; Barros de la Peña, Simón Alberto (Universidad Antonio Nariño, 2022)
Tourism in Colombia is one of the most booming sectors today. The tourism sector is considered as the attraction of a region with an eye on the national and international market, from the plans focused on the client interested in the practice of sports, cultural, artistic, natural or relaxation activities. At the level of natural and cultural tourism, the city of Santa Marta has the historical and archaeological attraction of the Lost City, a place located in the Sierra Nevada de Santa Marta, 60 kilometers away to reach it, the taste for having a vacation experience as close contact with nature and the geography of the region. The relationship of the Tayrona Indians with this cultural and historical richness dates back to that time, whose symbolic value for this community has great relevance to the preservation of the environment, ecology and respect for the customs of the native inhabitants of the region. It is in this scenario that strategic measures are required to preserve the integrity of the ecosystem, the comfort of the indigenous people and guarantee a conscious and adequate experience of tourism that represents the Lost City of Colombia. Thus, this strategic plan proposes alternatives and measures, both general and specific, focused on the development of responsible and sustainable tourism in the Lost City of Santa Marta.